2018
DOI: 10.1056/nejmoa1711948
|View full text |Cite
|
Sign up to set email alerts
|

Edoxaban for the Treatment of Cancer-Associated Venous Thromboembolism

Abstract: Oral edoxaban was noninferior to subcutaneous dalteparin with respect to the composite outcome of recurrent venous thromboembolism or major bleeding. The rate of recurrent venous thromboembolism was lower but the rate of major bleeding was higher with edoxaban than with dalteparin. (Funded by Daiichi Sankyo; Hokusai VTE Cancer ClinicalTrials.gov number, NCT02073682 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
1,134
11
62

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 1,345 publications
(1,240 citation statements)
references
References 16 publications
33
1,134
11
62
Order By: Relevance
“…However, in a randomised controlled trial (1050 patients with cancer-associated VTE) oral edoxaban was shown to be non-inferior to daltaparin in terms of VTE recurrence (non-inferiority P=0.006, 95% confidence interval 0.70 to 1.36), but with a higher rate of major bleeding (P=0.04, 95% confidence interval 1.03 to 3.04) 42. More investigation is needed before recommending DOACs in cancer-associated VTE.…”
Section: How Is It Treated?mentioning
confidence: 98%
“…However, in a randomised controlled trial (1050 patients with cancer-associated VTE) oral edoxaban was shown to be non-inferior to daltaparin in terms of VTE recurrence (non-inferiority P=0.006, 95% confidence interval 0.70 to 1.36), but with a higher rate of major bleeding (P=0.04, 95% confidence interval 1.03 to 3.04) 42. More investigation is needed before recommending DOACs in cancer-associated VTE.…”
Section: How Is It Treated?mentioning
confidence: 98%
“…Both higher‐dose (HDER) and lower‐dose (LDER) edoxaban regimens were noninferior to well‐managed warfarin in preventing stroke or systemic embolic events (SEEs) in patients with AF, and both regimens reduced bleeding and cardiovascular death 22. To date, data are sparse in patients treated with edoxaban who have both AF and malignancy, although a recent randomized trial in 1046 patients with venous thromboembolism and malignancy showed that edoxaban was noninferior to dalteparin in the prevention of recurrent venous thromboembolism but was associated with a 2.9% absolute increase in the rate of major bleeding 23. In the present analysis, we evaluate the safety and efficacy of edoxaban compared with warfarin in patients with AF who have developed a new or recurrent malignancy, with particular focus on the HDER because this is the regimen approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…The Hokusai VTE-Cancer Study is a multinational, open label, blinded outcome assessment RCT that compared 5 days of dalteparin followed by direct oral anticoagulant, edoxaban (60 mg daily) with dalteparin (200 IU/kg daily for 1 month followed by 150 IU/kg daily) for treatment of cancer-associated VTE 4. Edoxaban was reduced to 30 mg daily if patients had a creatinine clearance of 30–50 mL/hour, body weight <60 kg or required a P-glycoprotein inhibitor.…”
Section: Methodsmentioning
confidence: 99%